1.3: A Timing Model for the Design of an Active‐Matrix Display. (4th October 2019) - Xia, Zhihe; Lu, Xuchi; Lu, Lei; Li, Jiapeng; Kwok, Hoi Sing; Wong, Man
Abstract : A timing model for the design of an AM display was established integrally considering the charging process and delay propagating in the AM FPD driving. Based on the model, the bottle neck of different size FPDs was analyzed.